1992
DOI: 10.7164/antibiotics.45.1451
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal cyclic peptides from the terrestrial blue-green alga Anabaena laxa. I. Isolation and biological properties.

Abstract: Laxaphycins are responsible for the antifungal and cytotoxic activity of crude ethanolic extracts from the cultured blue-green alga Anabaena laxa. These cyclic peptides exhibit an unusual biological synergism when tested for antifungal or cytotoxic effects. The isolation procedure for the peptides, their characterization and biological activities are described here along with experiments demonstrating synergism between the two major laxaphycins. 1451Blue-green algae (cyanobacteria) have been recognized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 15 publications
2
92
0
1
Order By: Relevance
“…Discussion Synergistic Antifungal Activity. Cyanobacteria are known to produce lipopeptides with antifungal activity, such as nostofungicidine (18), laxaphycins (19)(20)(21), lobocyclamides (22), and hassallidins (14,23,24). In this study, we show that anabaenolysins have a weak antifungal activity (Fig.…”
Section: Significancementioning
confidence: 51%
“…Discussion Synergistic Antifungal Activity. Cyanobacteria are known to produce lipopeptides with antifungal activity, such as nostofungicidine (18), laxaphycins (19)(20)(21), lobocyclamides (22), and hassallidins (14,23,24). In this study, we show that anabaenolysins have a weak antifungal activity (Fig.…”
Section: Significancementioning
confidence: 51%
“…These, however, display distinct peptidic sequences. A similar situation was described in the synergistic antifungal activity of two classes of cyclic peptides obtained from the freshwater cyanobacterium Anabaena laxa (48). Other examples include the proteic "binary toxin" systems of several gram-positive bacteria, most notably the anthrax toxin (49).…”
Section: Discussionmentioning
confidence: 86%
“…The production of toxins and qualitative and quantitative information on the regulation of genes involved in toxin synthesis have revealed that a differential expression occurs in response to light quality and quantity, growth phase and chemical stressors (Carmichael 1994). Terrestrial cyanobacteria such as Anabaena laxa produce antifungal cyclic peptides such as laxaphycin A and B (Frankmolle et al 1992). Kulik (1995) reported that extracts from the cyanobacterium Nostoc muscorum Agardh inhibited the in vitro growth of the fungal plant pathogens such as Sclerotinia sclerotiorum (Cottony rot of vegetables and flowers) and Rhizoctonia solani (root and stem rots).…”
Section: Introductionmentioning
confidence: 99%